Effect of Early Water Deficits on Nodulation and Nitrogen Content of Inoculated Soybean (Bangladesh Agronomy Journal, 2018)
The study was conducted at the University of KwaZulu-Natal (29o37’ S, 30o23’ E) from May to November 2012 under controlled environment conditions with three water regimes namely: well watered controls, mild water stress to -1.4 MPa and severe water stress to -2.0 MPa, at the V4 (28 DAS) and V5 stages (35 DAS). Severe stress significantly reduced no. of nodule and root mass, leaf area, shoot dry mass and uptake, regardless of the stage. Mild stress on the other hand had little effect on this parameter as plants recovered on re-watering, to attain values similar to the control treatments. The V4 and V5 stages can recover from mild stress, but severe stress at both growth stages reduces nodulation and nitrogen uptake and this can lead to reduction in production potential of soybean.Bangladesh Agron. J. 2017, 20(2): 11-16